2021
DOI: 10.17515/resm2021.322st0702
|View full text |Cite
|
Sign up to set email alerts
|

Influence due to interface in finite element modeling of soil-structure interaction system: a study considering modified interface element

Abstract: The finite element (FE) modeling of interface in Soil-Structure Interaction (SSI) problem is most important aspect from early days of modeling i.e. during 1960. The overall performance of the structure is completely influenced due to behavior of interface. Such as realistic interface modeling of SSI system subjected to lateral loads leads to appropriate evaluation of lateral sway and base shear stress. During recent times, many modifications have been done in interface modeling such as incorporation of slip an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…According to the reviewed literature, it has been reported that the thin layer interface is appropriately representing the physical state of the SSI problem than that of the zerothickness interface [5][6][7][8][9][10]. Also, it has been noted that due to the bottom roughness of the footing, the soil particles slip as well as roll because of lateral loads as a result the thin layer interface has formed [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…According to the reviewed literature, it has been reported that the thin layer interface is appropriately representing the physical state of the SSI problem than that of the zerothickness interface [5][6][7][8][9][10]. Also, it has been noted that due to the bottom roughness of the footing, the soil particles slip as well as roll because of lateral loads as a result the thin layer interface has formed [11][12][13].…”
Section: Introductionmentioning
confidence: 99%